Um método para a refatoração de software baseado em frameworks de domínio - Barros, Víctor Pedroso Ambiel (2015)
A domain framework consists of a set of classes that capture the knowledge and expertise in a particular problem domain and are created by groups of developers who often do not follow the correct application of object-oriented concepts. To improve flexibility, readability, reusability, scalability and maintainability of domain frameworks can use refactoring software. The refactoring process is facilitated when using specific methods for applying the refactoring techniques which ensures a better result in the final product. Refactoring methods in the literature or answer a specific programming language or are more comprehensive. This paper created a method refactoring with reference to the methods of literature, able to assist developers in refactoring applications built with domain frameworks concepts. The proposed method consists of three main steps: Understanding the system, Sort modules and Refactor modules. The difference between the proposed method and the literature is that it provides for metapatterns, inversion of control and use of refactoring tool in their steps. The case study in which the method was applied is the Framework of Sales Price Formation (FrameMK), developed by the Research Group Information Systems on Campus Ponta Grossa, which have the purpose of calculating the selling price of a product or service. The results of applying the method in FrameMK were: improved code complexity, reduces the quantity of bad smells and the duplication code, the code became more reusable and flexible and there was an increase in the quality of software in relation to expectations of its cycle life.